A descriptive study of safety leadership in manufacturing industry - Mohd. Najib, Bin Kamarudin (Universiti Malaysia Sarawak (UNIMAS), 2019)
The focus of the study is to explore the ef1ectiven(ess of roles of supervisors and managers at manufacturing industry. The effectiveness of the safety leadership is explored based on different level of analysis which are level of safety awareness, importance of safety leadership, roles of supervisors and managers in safety management, impact of safety leadership, and method to improve safety leadership. This study was conducted in a manufacturing plant in Kuching, Sarawak and the method adopted to collect data for the finding is interview. Data collection involves 4 respondents from various departments in the manufacturing plan which becomes respondents to analyze and generate the result for the findings. The result shows that there are multiple categories that can concluded from each level of data analysis. As example, there are two categories of importance of safety leadership at the organization which are influence safety culture and ensuring implementation of safety practice.